ANALISIS KESIAPAN MAHASISWA PENDIDIKAN GURU MADRASAH IBTIDAIYAH INSTITUT AGAMA ISLAM AL-ZAYTUN INDONESIA MENJADI GURU PROFESIONAL - Amelia Rohmatunisa, Nur; Peranginangin, Henri; Iswandi, Irvan (Sindoro: Cendikia Pendidikan, 2024)
The readiness of PGMI students of the 2021 batch of IAI AL-AZIS to become prospective professional teachers is a key factor in ensuring their success as educators in the future. A prospective professional teacher is expected to have adequate abilities based on learning achievements and four main competencies, namely pedagogical, social, personality, and professional competencies. Therefore, the purpose of this study is to determine the readiness of PGMI students of 2021 to become professional teachers in terms of physical and mental aspects and to analyze the completeness of the learning achievement results of PGMI students of 2021 who stated that they were ready to become professional teachers. This research method uses a qualitative descriptive approach. The subjects in this study were 10 PGMI students of the 2021 batch. The data collection techniques used in the study were observation, interviews, and documentation. Furthermore, the data was analyzed with the following steps: 1) data collection, 2) data reduction, 3) data presentation, 4) data verification. The results of the study showed that most PGMI 2021 IAI AL-AZIS students had good physical and mental readiness. As many as 90% of students stated their readiness to face their duties as teachers. Meanwhile, 92% of students showed the ability to manage learning and apply relevant methods. In terms of personality and general skills, 100% of students stated their readiness to be good role models for students. However, in terms of specific skills, student readiness reached 88%, so that the completion of the learning achievements of PGMI 2021 IAI AL-AZIS students to meet graduate competency standards was still not optimal. Keywords: Readiness, PGMI Students, Professional Teachers